CLIMATE CONTROL AND LIGHT CONTROL IN A SMART HOME - Jo’rayev Vohid Tojimamatovich; Xalilova Muhabbat Alimdjanovna (Journal Park Publishing, 2022)
This article examines "Management models of smart homes based on human functions" and provides information about the intelligent system of the "smart home". Currently, based on the development of technologies, many residential buildings are being automated, that is, "smart houses" are being built. Today, in the creation of a "smart home" system, technologies for controlling indicators such as air temperature, humidity level, atmospheric pressure and lighting level, as well as the level of home security are widely used.
Keywords: smart home, information, dimmers, motion sensors, ventilation, air purification